2, 3, 5, 4′-Tetrahydroxy-stilbene-2-O-beta-d-glucoside induces autophagy-mediated apoptosis in hepatocytes by upregulating miR-122 and inhibiting the PI3K/Akt/mTOR pathway: implications for its hepatotoxicity. (1st January 2020) - Yang, Lei; Xing, Wei; Xiao, Wang-Zhong; Tang, Lin; Wang, Lu; Liu, Meng-Jiao; Dai, Bing
Abstract: Context: The potential hepatotoxicity of Polygoni Multiflori Radix (PMR) has attracted much attention, but the specific mechanism of inducing hepatotoxicity is still unclear due to the complexity of its components. Objective: This study investigated the specific mechanism by which 2, 3, 5, 4′-tetrahydroxy-stilbene-2- O -β-d -glucoside (TSG) regulates hepatotoxicity. Materials and methods: The toxic effects of TSG (10, 100, 1000 μg/mL) on WRL-68 cells were examined using MTT, flow cytometry, and LDH assay after 24 h of incubation. Untreated cells served as the control. Gene and protein expression levels were determined by quantitative real-time PCR and Western blot, respectively. Immunofluorescence analysis was conducted to investigate the expression of light chain 3 (LC3). Luciferase activity assay was used to assess the targeted regulation of RUNX1 by miR-122. Results: The half maximal inhibitory concentration (IC50) of TSG in WRL-68 cells was calculated as 1198.62 μg/mL. TSG (1000 μg/mL) inhibited cell viability and LDH activity and promoted WRL-68 cell apoptosis by inducing autophagy. Subsequent findings showed that TSG induced autophagy and promoted apoptosis in WRL-68 cells by downregulating the levels of p-PI3K, p-Akt, and p-mTOR proteins, while RUNX1 overexpression rescued this inhibition. Additionally, the effect of TSG on hepatocyte apoptosis was reversed by miR-122 knockdown. Furthermore, bioinformatics and dual luciferase reporter assay results indicated that miR-122 targeted RUNX1. Discussion and conclusions: Our data demonstrate for the first time that TSG regulates hepatotoxicity, possibly by upregulating miR-122 and inhibiting the RUNX1-mediated PI3K/Akt/mTOR pathway to promote autophagy and induce hepatocyte apoptosis. Further in vivo research is necessary to verify our conclusion.